PERGESERAN PARADIGMA PEMBELAJARAN KEWIRAUSAHAAN - Kurjono - (Universitas Pendidikan Ganesha, 2013)
Penulisan ini dilatarbelakangi oleh suatu pemikiran tentang pemahaman konsep kewirausahaan yang selama ini dipahami para praktisi pendidikan bahwa kewirausahaan diidentifikasikan dengan belajar berbisnis. Padahal belajar berbisnis hanya salah satu aspek dari berwirausaha. Inti masalah yang hendak diungkapkan adalah sejauh manakah pemahaman dan pelaksanaan pendidikan kewirausahaan dapat merubah kondidi sosial masyarakat. Hal penting yang harus dipahami para pelaksana pendidikan adalah lebih menekankan aspek pembinaan mentalitas individu peserta didik, mengingat siswa sebagai peserta didik masih dalam proses internalisasi. Pergeseran paradigma ini sangat tepat untuk meletakkan sesungguhnya pola apa yang harus ditekankan dalam pembelajaran kewirausahan. Dari hasil pemikiran dan perenungan kondisi saat ini maka penulis menekaknkan pentingnya mengantisipasi pergeseran paradigma ini, agar pembelajaran kewirausahaan yang selama ini dilaksanakan tidak condong menggiring peserta didik untuk menjadi pebisnis/pedagang atau penyelenggara sektor jasa saja, namun aspek kegiatan manusia yang meliputi usaha sektor jasa, perdagangan dan manufaktur maupun dalam profesi lainnya sehingga dapat dijadikan bekal dan pegangan peserta didik kelak setelah mereka lulus dari jenjang sekolahnya. Berdasarkan penjelasan tersebut, maka dapat dilakukan pola pembelajaran kewirausahaan yang lebih bermakna bagi siswa terutama menanamkan sikap kreatif dan sikap inovatif sebagai modal dasar siswa untuk berwirausaha. Kata Kunci : Pergeseran, Kewirausahaan, Peserta didik, Sikap Kreatif dan Sikap Inovatif ABSTRACT The writing is motivated by an understanding of the concept of entrepreneurial thinking that has been understood that education practitioners identified by studying business entrepreneurship. Though learning to do business only one aspect of entrepreneurship. Core issues to be disclosed is the extent to which the understanding and implementation of entrepreneurship education can change society through the phenomenon of social conditions of high unemployment especially among college students.It is important to understand the implementation of education relating to entrepreneurship should be more emphasis on the development of the mentality of the individual learners. Considering students as learners are still in the process of internalization, the paradigm shift is very appropriate to put the actual pattern of what should be emphasized in both entrepreneurial learning in basic education high school students and college studentsReflection of the ideas and the current state of the author outlines the common thread is the importance of anticipating the paradigm shift that entrepreneurial learning which has been implemented is not inclined lead learners to become businessman / merchant or service provider sector alone, but human activities covering aspects of business sector services, trade and manufacturing as well as in other professions that can be used as a grip stock and future students after they graduate from school level. Given that not all students are interested in becoming a merchant.Based on these explanations, it can be done pattern entrepreneurial learning more meaningful for students especially inculcate creative and innovative attitude attitude as basic capital for entrepreneurship students in various professions both in the private as well as public servants so as expectations of learners can develop entrepreneurship in various jobs. Key word: Education, entrepreneurship, creative, innovative